Menumbuhkan Tingkat Kesadaran Pengaruh Teknologi Informasi Serta Media Internet Terhadap Remaja dan Anak-Anak - Sandhy Fernandez; Cahyo Prihantoro; Dedy Agung Prabowo (Join, 2022)
With the presence of the internet which is the development of communication and information technology, it is easier to access various information internationally. The internet is a source of learning for the community, because by using the internet people can access information quickly and easily. Even various sources of information from various media can be modified via the internet. With the internet that can affect the good and bad sides of internet users, especially among teenagers and children, it can attract our attention to carry out this service activity. The purpose of this activity is to increase knowledge about the influence of the internet on its users and increase knowledge about the positive and negative impacts of the internet for teenagers. Seeing the negative and positive impacts of information and communication technology, especially the Internet, above. The method used in this activity is to convey directly to children and adolescents and also apply methods such as educational games that can increase the enthusiasm for learning for children and adolescents. This activity was carried out at the Al-Maun Shelter, Bengkulu City, targeting children and adolescents. It can be concluded that when compared to the negative impacts, the positive impacts are far more numerous, so it is impossible for it to be banned in Indonesia. Suggestions that can be given are after the implementation of this activity so that children and adolescents are wise in using internet services and as much as possible the role of parents to supervise activities in accessing the internet